1974
DOI: 10.1111/j.1432-1033.1974.tb03611.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Labile Products of Mitochondrial Protein Synthesis in vitro

Abstract: 1. This paper describes some features of the protein synthesis in isolated rat liver mitochondria and reports on the stability of the product of mitochondrial protein synthesis in vitro. 2. Chase experiments performed after a 30‐min pulse of [14C]leucine indicated that a large part of the product is degraded to an acid‐soluble form (labile product) almost as rapidly as it is terminated and released from the mitoribosome. Only a small proportion of the completed product (between 20 and 40 %) is conversed in aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…Although Tzagoloff and Akai [28] and Wheeldon et al [39] have reported single low-molecular-weight moieties in yeast and rat liver, respectively, the data of Kuntzel and Blossey [38] and the higher resolution allowed by the autoradiographic procedure used here shows two labelled components. The bands as they appear on the gels of Tzagoloff and Akai and Wheeldon et al are broad and possibly could be resolved into two bands.…”
Section: Analysis Of the Products Of Mitochondria1 Protein Synthesismentioning
confidence: 47%
“…Although Tzagoloff and Akai [28] and Wheeldon et al [39] have reported single low-molecular-weight moieties in yeast and rat liver, respectively, the data of Kuntzel and Blossey [38] and the higher resolution allowed by the autoradiographic procedure used here shows two labelled components. The bands as they appear on the gels of Tzagoloff and Akai and Wheeldon et al are broad and possibly could be resolved into two bands.…”
Section: Analysis Of the Products Of Mitochondria1 Protein Synthesismentioning
confidence: 47%
“…The same holds for chloramphenicol, an inhibitor of mitochondrial translation (Wheeldon et al 1974;Kalnov et al 1979b;Black-Schaefer et al 1991), and hemin . It is unclear at present why chloramphenicol should inhibit degradation, as other inhibitors of translation do not have this effect .…”
Section: Characterization Of the Proteolytic Systemmentioning
confidence: 79%
“…Black-Schaefer et al (1991) also observed two pools with different rates of turnover, one with a half-life of minutes, the other with a half-life of hours. Instability of (a subset of) mitochondrial translation products has also been observed in rat liver mitochondria (Wheeldon et al 1974;Desautels and Goldberg 1982b), as well as in HeLa cells and rat hepatoma cells in the presence of cycloheximide (Constantino and Attardi 1977;Hall and Hare 1990). As assembly of mitochondrially encoded subunits of inner membrane complexes depends on the presence of imported subunits, and these imported subunits will become limiting at some point in isolated mitochondria or when cytoplasmic translation is inhibited, the rapidly degraded mitochondrial translation products probably represent unassembled subunits.…”
Section: Degradation Of Mitochondrial Translation Productsmentioning
confidence: 92%
“…Furthermore, such "precursor" polypeptides seem to be soluble in chloroform-methanol [8,28]. Thus it is well possible that mitochondrial proteins soluble in chloroform -methanol contain short-lived precursors, but from the data shown here it is clear that at least the proteins of peak1 are stable, mature products of intramitochondrial protein synthesis.…”
Section: Discussionmentioning
confidence: 93%